Living with psychosis: strategies and social conditions for recovery. Issue 2 (3rd April 2018) - Georgaca, Eugenie; Zissi, Anastasia
ABSTRACT: The paper examines the often neglected, social factors implicated in recovery from severe mental distress, by presenting findings from a biographical study of individuals experiencing psychosis. Biographical interviews with 26 individuals with psychotic experiences and diagnosis of psychotic disorders were conducted and subjected to narrative biographical analysis. This paper focuses on a group of narrators who are engaged in a struggle to live a satisfactory life despite ongoing mental distress, and thus can be seen as being in recovery. In terms of therapeutic itineraries, the distinctive characteristics of this group are the early recognition and community management of psychotic experiences. Participants in this group also consistently employ various strategies for managing their psychotic experiences as well as for looking after their mental health. The two most central social parameters for recovery identified in this study are firstly, increased social participation through interpersonal and social networks, and secondly, access to empowering discourses and practices regarding mental distress, which are in turn related to developments in the mental health service system over the last two decades. We conclude that crucial parameters in building a life with psychosis involve the broader sociocultural context, the mental health service system, and familial and social networks.